2020
DOI: 10.3389/fmed.2020.588967
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Arterial Stiffness Increases the Risk of Progression of Renal Disease in Type 2 Diabetic Patients

Abstract: Aims: Our aim was to investigate the effects of peripheral arterial stiffness on the risk of progression of renal disease in patients with type 2 diabetes (T2D). Methods: This was a single center, retrospective cohort study. Brachial-ankle pulse wave velocity (baPWV) tests were performed on T2D patients in 2015. Increased arterial stiffness was defined as baPWV of ≥ 1800 cm/s. We applied criteria for progression of renal disease according to EMPA-REG OUTCOME trial. Results: In total, 186 patients were enrolled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…We found that the cumulative incidence of new-onset renal damage and isolated proteinuria in the normal arterial stiffness group, borderline atherosclerosis group, and arteriosclerosis group increased gradually, from 6.71% and 4.79% in the normal group to 15.84% and 11.31% in the atherosclerosis group, respectively. Similar to our follow-up time and age, Lim et al [8] also found a higher cumulative incidence of new renal damage in the Model 2 was further adjusted for smoking status (never smoker, past or current smoker), drinking status (never drink, past or current drink), salt status (light and common salt, heavy salt), physical activity (low or moderate, high), educational level (primary or middle, college); Model 3 was further adjusted for MAP (mmHg), FBG (mmol/L), TC (mmol/L), body mass index (kg/m 2 ), uric acid (umol/L), CRP (mg/L), eGFR (mL/min/1.73 m 2 ), the duration of diabetes (year), using antihypertensive drugs (no, yes), using hypoglycemic drugs (no, yes), using hypolipemic drugs (no, yes).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…We found that the cumulative incidence of new-onset renal damage and isolated proteinuria in the normal arterial stiffness group, borderline atherosclerosis group, and arteriosclerosis group increased gradually, from 6.71% and 4.79% in the normal group to 15.84% and 11.31% in the atherosclerosis group, respectively. Similar to our follow-up time and age, Lim et al [8] also found a higher cumulative incidence of new renal damage in the Model 2 was further adjusted for smoking status (never smoker, past or current smoker), drinking status (never drink, past or current drink), salt status (light and common salt, heavy salt), physical activity (low or moderate, high), educational level (primary or middle, college); Model 3 was further adjusted for MAP (mmHg), FBG (mmol/L), TC (mmol/L), body mass index (kg/m 2 ), uric acid (umol/L), CRP (mg/L), eGFR (mL/min/1.73 m 2 ), the duration of diabetes (year), using antihypertensive drugs (no, yes), using hypoglycemic drugs (no, yes), using hypolipemic drugs (no, yes).…”
Section: Discussionsupporting
confidence: 89%
“…In addition, a study [7] of 461 Japanese DM patients revealed that cf-PWV had an independent association with a faster decline in kidney function. In contrast, a study [8] of 186 South Korea DM patients, showed a negative correlation between PWV and annual change in eGFR, whereas no signifificant risk was observed for the decline in eGFR among individuals with a BaPWV of ≥1,800 cm/s (HR 2.76, 95% CI 0.15-52.07). However, such results should be interpreted with caution because of small sample size.…”
Section: Endocrine Journal Advance Publicationmentioning
confidence: 82%
See 1 more Smart Citation
“…The correlation between these three features is analyzed to find the risk of diabetes patients with increased arterial stiffness. Lim et al, [13] studied the increased arterial stiffness leading to renal diseases in Type 2 diabetes mellitus using baPWV. Based on the EMPA-REG-Outcome trial, the increased risk of arterial stiffness is defined as baPWV>=1800 cm/s.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Pulse Wave Velocity (PWV), the propagation velocity of blood waves/pulses via the circulatory system, is a strong indicator of arterial stiffness [8][9][10][11] and can be used for the prediction of cardiovascular events [12]. The magnitude of PWV highly depends on the property of the blood vessels, e.g., blood vessel elasticity and wall thickness [13].…”
Section: Introductionmentioning
confidence: 99%